Distributionally sensitive cost-benefit analysis - Robin W. Boadway; Michael Smart (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We propose a method for cost-benefit analysis of public policies that identifies potential Pareto improvements when losers from a reform are compensated through income tax changes. Reforms are desirable when they reduce aggregate excess burden in commodity and labor markets. This condition is equivalent to a weighted sum of individual compensating variations, where weights reflect the impacts of the policy reform on individuals' labor incomes, rather than marginal social valuations of transfers to them. We identify cases in which distributional weights are increasing in individual incomes, despite inequality concerns.
Keywords: D60; H20; H40; I30; 330; applied welfare economics; weighted surplus; excess burden